การวิเคราะห์การยอมรับและพฤติกรรมการปฏิบัติงานของครูหลังการประเมินความรู้ครูของกระทรวงศึกษาธิการ - ฑิตยา สิทธิโสภาสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To (1) study teacher’s acceptance level and performance behaviours level after assessment of teacher knowledge (2) analyze and compare acceptance level and performance behaviours level among teachers who had different backgrounds and who participated in knowledge assessment of different subjects, (3) compare teacher’s performance behaviours before and after assessment of teacher knowledge, and (4) analyze teacher’s acceptance level affecting performance behaviours after assessment of teacher knowledge. The researcher conducted mixed-methods research and sequential mixed-methods design. Firstly, 460 teachers in Bangkok area were asked to participate in their knowledge assessment by using questionnaire to collect qualitative data. The second stages is quantitative data collection by using in-depth interview. Qualitative data were analyzed by employing frequency, percentage, means, standard deviation, cross-tabulation, paired t-test, one-way MANOVA, factor analysis, and LISREL model analysis. Quantitative data were analyzed by content analysis. The research findings were as follows: (1)Teacher’s acceptance in testing process and assessment result of teacher knowledge was at moderate level. After assessment of teacher knowledge, teacher’s performance behaviours were improved in terms of self development, development of learning management and professional development at high level. (2) Teachers who had different ages, teaching experiences, training experiences, assessment result of knowledge had different acceptance level of knowledge assessment and performance behaviours at the 0.05 level of significance. In contrast, teachers who had different educational levels, teaching levels and subjects assessed their knowledge had indifferent acceptance level of knowledge assessment and performance behaviours. Teachers who had different positions had different performance behaviours at the 0.05 level of significance but indifferent acceptance level of knowledge assessment. (3) There was difference between performance behaviours before and after assessment of teacher knowledge at the 0.01 level of significance. Results found that teachers improved their performance behaviours in terms of self-development, development of learning management, professional development after assessment of teacher knowledge. (4) Teacher’s acceptance in knowledge assessment process affected performance behaviours after assessment of teacher knowledge. This could explain 23.30% of the variances and 0.482 in effect size.